Modelos de simulación para el análisis del comportamiento del sector energético en Colombia promoviendo la transición energética (2024)
The development of the document exposes scenarios associated with difficulties and factors that directly affect the energy transition in Colombia through a dynamic model. In this way, a base information was established, collected from entities in charge of the production and regulation of the energy resource such as the Mining-Energy Planning Unit (UPME) and Xm, which is the administrator of the energy market in Colombia from which a causal model for the analysis of energy use in the Colombian population, such as generation costs and effects on the environment.